2014
DOI: 10.5539/hes.v4n2p42
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Critical Thinking in Professional and Academic Bachelor Programmes

Abstract: Critical thinking is an important goal in higher education. Students are expected to grow in critical thinking during their higher education programme. The present study investigates the development of critical thinking in 1134 bachelor students in Flanders, Belgium. The study followed a mixed longitudinal design. Students' critical thinking was measured by the Scipio, a test consisting of both constructed response items and forced choice items. The analyses were split up for academic and professional bachelor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…A considerable amount of literature has been published on the importance of critical thinking skills in higher education (Surlitasari & Premini, 2018;Mbato, 2019;Van der Zanden et al, 2020;Gandimathi & Zarei, 2018). These studies have found that cognitive skills are central to critical thinking; these skills include recognizing logical fallacies analyzing arguments, distinguishing warranted and unwarranted claims, and identifying and understanding assumptions in scientific-analytical reasoning (Evens et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A considerable amount of literature has been published on the importance of critical thinking skills in higher education (Surlitasari & Premini, 2018;Mbato, 2019;Van der Zanden et al, 2020;Gandimathi & Zarei, 2018). These studies have found that cognitive skills are central to critical thinking; these skills include recognizing logical fallacies analyzing arguments, distinguishing warranted and unwarranted claims, and identifying and understanding assumptions in scientific-analytical reasoning (Evens et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our paper suggests a more practical approach to future language scholar training in comparative pedagogy that is more innovative. A good example is how Venn diagrams can be used to represent the four categorical form statements, A-, E-, I-, and O-forms, and other assignments proposed by Cohen (2009). Fig.…”
Section: Challenges Of Comparative Pedagogy Training In Ukrainementioning
confidence: 99%
“…Teaching and learning critical thinking skills is a complex process which among other important aspects is shaped by teacher and students understanding of critical thinking. The importance of developing critical thinking skills and the challenges faced by teachers in the study process have been drawing the attention of researchers around the world (Evens et al, 2014;Gillespie & McBain, 2014). Researchers argue that critical thinking can be learned, encouraged, and developed (Niu et al, 2013;Abrami et al, 2015, Veliz & Veliz-Campos, 2019Puig et al, 2019).…”
Section: Introductionmentioning
confidence: 99%